2021
DOI: 10.3390/ijerph18041556
|View full text |Cite
|
Sign up to set email alerts
|

Access to Dental Care—A Survey from Dentists, People with Disabilities and Caregivers

Abstract: The literature highlights differences in the dental conditions of people with disabilities compared with the general population. The aim of this study was to provide an overview of the dental health of people with disabilities in order to understand if their needs are met and to identify their most critical issues as per dentists. A paper and a Google Form platform were used in conducting a survey in Central Italy (the Abruzzo region), by performing an analysis on different points of view as reported by people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 29 publications
2
25
0
2
Order By: Relevance
“…21.7% of patients have not undergone dental screening for more than 5 years. Patients with physical disabilities have limited access to dental care due to difficulty in finding barrier free dental offices [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…21.7% of patients have not undergone dental screening for more than 5 years. Patients with physical disabilities have limited access to dental care due to difficulty in finding barrier free dental offices [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not include disabled people among the categories of social vulnerability, as they may be affected by a double vulnerability, social and sanitary, at the same time. However, it must be taken into account that social and medical vulnerability combined increase the risk factors for caries and periodontal disease [ 209 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a worse quality of life in patients with compromised oral health especially in children with special needs [ 49 , 50 ]. In addition, people with disabilities report difficulties accessing dental care and finding specialized dentists and barrier-free dental offices [ 51 ]. Oral prevention, namely treatment and maintenance programs associated with careful oral hygiene procedures carried out at home, is essential to prevent oral diseases, especially in patients with rare genetic syndromes.…”
Section: Discussionmentioning
confidence: 99%